2023
DOI: 10.1007/s10530-022-02982-5
|View full text |Cite|
|
Sign up to set email alerts
|

Global invasion history and native decline of the common starling: insights through genetics

Abstract: Few invasive birds are as globally successful as the Common or European Starling (Sturnus vulgaris). Native to the Palearctic, the starling has been intentionally introduced to North and South America, South Africa, Australia, and the Pacific Islands, enabling us to explore species traits that may contribute to its invasion success. Coupling the rich studies of life history and more recent explorations of genomic variation among invasions, we illustrate how eco-evolutionary dynamics shape the invasion success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Therefore, comparisons of genetic diversity between native and invasive ranges are currently provisional. Relatedly, the source population for many of these introductions is historically documented as Britain, but this has not been confirmed with genetic data 7 . Comparisons between invasive ranges show that North America (NA) harbors higher mitochondrial haplotype diversity than Australia or South Africa, which may be due to rapid expansion in NA facilitated by climate matching with the native range.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, comparisons of genetic diversity between native and invasive ranges are currently provisional. Relatedly, the source population for many of these introductions is historically documented as Britain, but this has not been confirmed with genetic data 7 . Comparisons between invasive ranges show that North America (NA) harbors higher mitochondrial haplotype diversity than Australia or South Africa, which may be due to rapid expansion in NA facilitated by climate matching with the native range.…”
Section: Introductionmentioning
confidence: 96%
“…There are ten recorded starling introductions to North America 7 . According to historical records, the only populations which became established were those from the introductions to New York (1890, 1891) and Oregon (1889, 1892).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are distributed across a wide range of habitat and are rarely migratory, although, some Starlings, especially hatching-year individuals, migrate up to several hundred miles (Johnson & Glahn, 1994). A plethora of studies have suggested decline in Starling bird population (Callaghan et al, 2021;Crick et al, 2002;Robinson et al, 2005;Stuart et al, 2023;Svensson, 2004). This study aimed to determine Starling species diversity and abundance, along with vegetation and seasonal variations at Federal University Dutse.…”
Section: Introductionmentioning
confidence: 97%
“…Further, the common myna is a relative of the European starling ( Sturnus vulgaris ), another globally invasive passerine with a similar introduction history. 29 Such interspecies comparisons will provide an opportunity to examine whether molecular evolutionary processes behave in a conserved or stochastic manner across invasions of similar phylogenetic, ecological, and historical nature.…”
Section: Introductionmentioning
confidence: 99%